Herceptin Enhances the Antitumor Effect of Natural Killer Cells on Breast Cancer Cells Expressing Human Epidermal Growth Factor Receptor-2 - Tian, Xiao; Wei, Feng; Wang, Limei; Yu, Wenwen; Zhang, Naining; Zhang, Xinwei; Han, Ying; Yu, Jinpu; Ren, Xiubao (Frontiers in Immunology, 2017)
Optimal adoptive cell therapy should contribute to effective cancer treatment. The unique ability of natural killer (NK) cells to kill cancer cells independent of major histocompatibility requirement makes them suitable as adoptive cell therapy tools. Herceptin, an anti-human epidermal growth factor receptor-2 (HER2) monoclonal antibody, is used to treat HER2+ breast cancer. However, it has limited effectiveness and possible severe cardiotoxicity. Given that Herceptin may increase the cytotoxicity of lymphocytes, we explored the possible augmentation of NK cell cytotoxicity against HER2+ breast cancer cells by Herceptin. We demonstrated that Herceptin could interact with CD16 on NK cells to expand the cytotoxic NK (specifically, CD56dim) cell population. Additionally, Herceptin increased NK cell migration and cytotoxicity against HER2+ breast cancer cells. In a pilot study, Herceptin-treated NK cells shrunk lung nodular metastasis in a woman with HER2+ breast cancer who could not tolerate the cardiotoxic side effects of Herceptin. Our findings support the therapeutic potential of Herceptin-treated NK cells in patients with HER2+ and Herceptin-intolerant breast cancer.